Biotin analogues with antibacterial activity are potent inhibitors of biotin protein ligase - Tieu, William (2013)
There is a desperate need to develop new antibiotic agents to combat the rise of drug-resistant bacteria, such as clinically important Staphylococcus aureus. The essential multifunctional enzyme, biotin protein ligase (BPL), is one potential drug target for new antibiotics. We report the synthesis and characterization of a series of biotin analogues with activity against BPLs from S. aureus, Escherichia coli, and Homo sapiens. Two potent inhibitors with Ki < 100 nM were identified with antibacterial activity against a panel of clinical isolates of S. aureus (MIC 2–16 μg/mL). Compounds with high ligand efficiency and >20-fold selectivity between the isozymes were identified and characterized. The antibacterial mode of action was shown to be via inhibition of BPL. The bimolecular interactions between the BPL and the inhibitors were defined by surface plasmon resonance studies and X-ray crystallography. These findings pave the way for second-generation inhibitors and antibiotics with greater potency and selectivity.